Validation of a 4‐item subjective cognitive decline screening questionnaire in cognitively normal older adults. (31st December 2021) - Strenger, Jennifer; Alber, Jessica; Arthur, Edmund; Snyder, Peter J; Sinoff, Stuart; Correia, Stephen; Salloway, Stephen P.; Thompson, Louisa I
Abstract: Background: Subjective cognitive decline is an important factor in understanding AD risk and the progression of preclinical AD. Recent efforts have formalized a framework for defining and researching SCD, but significant variability still exists in the assessment and quantification of SCD (Jessen et al., 2014; Molinuevo et al., 2017). Including a uniform assessment of core defining SCD features in AD clinical research could help to overcome this problem and generalize research findings. We report preliminary data validating the novel Subjective Cognitive Decline Screen (SCDS), a 4‐item scale designed to assess key features of SCD in preclinical AD, as described by the Subjective Cognitive Decline Initiative (SCD‐I) Working Group. Method: Participants were 97 cognitively unimpaired adults (ages 55‐80, 68% female, 93% White) pooled across two ongoing observational AD studies. The SCDS consists of 4 self‐report multiple choice questions assessing concerns about memory (0‐2 points), extent of memory decline (0‐2 points), and perceived memory change relative to peers (0‐1 point), with total scores ranging from 0 (no SCD) to 5 (high SCD). Result: A total of 67% of participants endorsed at least one SCDS item. Total scores ranged from 0 to 5 ( M = 1.3, SD = 1.4) and did not vary significantly on the basis of sex, age, or education. The SCDS demonstrated fairly high internal consistency overall (4 items; Cronbach's α = .79), with an average inter‐item correlation of r = .48. The scale was positively correlated with the self‐report form of the Cognitive Function Index (CFI; Amariglio et al., 2015), a 14‐item measure of SCD widely used in AD research (r = .68, p < .01). In sub‐analyses of participants with known APOE genotype (n = 46) and known amyloid PET status (n= 25), SCDS scores did not differentiate APOE e4 carrier or amyloid PET status, respectively. Conclusion: Our initial evidence suggests that the SCDS is a convenient tool for brief SCD assessment with fairly high internal consistency, though the average inter‐item correlation suggests some overlap in item content. Further work is needed to validate the scale in more racially and culturally diverse samples and in individuals with biomarker defined preclinical AD.